2009
DOI: 10.1016/j.atherosclerosis.2009.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal treatment influences risk markers for atherosclerosis in patients with severe periodontitis

Abstract: a b s t r a c tThis study investigated the effect of mechanical infection control for periodontitis and periodontal surgery on the prevalence of well-established risk factors for atherosclerosis, and plasma levels of cytokines, antibodies against heat shock proteins and markers of systemic inflammation.Sixty-eight patients between 39 and 73 years of age with severe periodontitis who had been referred to four specialist periodontology clinics in Sweden were investigated. A fasting venous blood sample was taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 27 publications
(28 reference statements)
6
57
0
2
Order By: Relevance
“…In support of a causal relationship, it has been claimed that periodontal treatment lowers C-reactive protein and low-density lipoproteins and improves endothelial function. [12][13][14][15] Such findings, addressing surrogate end points and not cardiovascular events, must be interpreted with caution, leaving an uncertainty regarding the true nature of the association between periodontal and cardiovascular disease. This knowledge gap was recently recognized by the American Heart Association in the following way …"statements that imply a causative association between periodontal disease and specific atherosclerotic vascular disease events or claim that therapeutic interventions may be useful on the basis of that assumption are unwarranted."…”
mentioning
confidence: 99%
“…In support of a causal relationship, it has been claimed that periodontal treatment lowers C-reactive protein and low-density lipoproteins and improves endothelial function. [12][13][14][15] Such findings, addressing surrogate end points and not cardiovascular events, must be interpreted with caution, leaving an uncertainty regarding the true nature of the association between periodontal and cardiovascular disease. This knowledge gap was recently recognized by the American Heart Association in the following way …"statements that imply a causative association between periodontal disease and specific atherosclerotic vascular disease events or claim that therapeutic interventions may be useful on the basis of that assumption are unwarranted."…”
mentioning
confidence: 99%
“…Periodontal therapy can reduce the levels of pro-inflammory cytokines at three months post-therapy, and thus may lower the CVD incidence. In addition, the current study concluded that periodontal therapy had minimal impact on levels of TNF-α and IL-1β [37]. The effects of periodontal intervention on serum IL-6 are not consistent.…”
Section: Effects Of Periodontal Intervention On Inflammatory Cytokinesmentioning
confidence: 68%
“…In a study where successful periodontal treatment with pocket reduction was reported in adult periodontal patients with severe periodontitis, serum glucose, lipids and markers of systemic inflammation were not significantly altered after 3 months. At one year, HDL-C concentrations were significantly increased and LDL-C concentrations decreased with concurrent reduction in IL-18 and interferon  levels (Buhlin et al 2009). Both mechanical periodontal debridement and treatment with a nonsteroidal anti-inflammatory drug appeared to affect serum glycoprotein markers of infection and inflammation.…”
Section: Associations Of Periodontal Disease With Coronary Heart Diseasementioning
confidence: 89%